2011
DOI: 10.5194/amt-4-1603-2011
|View full text |Cite
|
Sign up to set email alerts
|

Near-surface profiles of aerosol number concentration and temperature over the Arctic Ocean

Abstract: Abstract. Temperature and particle number concentration profiles were measured at small height intervals above open and frozen leads and snow surfaces in the central Arctic. The device used was a gradient pole designed to investigate potential particle sources over the central Arctic Ocean. The collected data were fitted according to basic logarithmic flux-profile relationships to calculate the sensible heat flux and particle deposition velocity. Independent measurements by the eddy covariance technique were c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…The observed number size distribution for all HP (Fig. 5, lower panel) is in agreement with results from the high Arctic reported by Hillamo et al (2001), who observed the first maximum in sulfate-containing aerosol particles at diameters > 80 nm and in ammonium and MSA-containing particles at diameters > 100 nm.…”
Section: Halo Particlessupporting
confidence: 91%
“…The observed number size distribution for all HP (Fig. 5, lower panel) is in agreement with results from the high Arctic reported by Hillamo et al (2001), who observed the first maximum in sulfate-containing aerosol particles at diameters > 80 nm and in ammonium and MSA-containing particles at diameters > 100 nm.…”
Section: Halo Particlessupporting
confidence: 91%
“…Simultaneous and independent gradient measurements of particle concentrations presented in Held et al (2011b) corroborate the finding that open leads can indeed act as particle sources in the Arctic Ocean. Overall, the direct contribution of the open lead particle emissions to the atmospheric aerosol number concentration could only explain a few percent of the observed total particle number variability measured onboard the ship.…”
Section: Aerosol Transport Over the Pack Icesupporting
confidence: 68%
“…With the suggestion from the previous expeditions that an unknown fraction of airborne and in-cloud aerosol were polymer gels originating either in local open water leads or from a distant source, such as the MIZ, an attempt was made to quantify the net contribution of the local lead aerosol flux to the observed aerosol concentrations. Direct eddy covariance observations of the net aerosol flux into the atmosphere were performed at the ice edge near the "Open Lead" site (Held et al, 2011a); the results compared well with independent estimates obtained from aerosol concentration gradients very close to the water surface (Held et al, 2011b).…”
Section: Aerosols In Air and In Cloud Dropletsmentioning
confidence: 70%
“…The response time of the particle counter, including the sampling line, was approximately 1.4 s. Near-surface profiles of aerosol number concentration and temperature were also measured using a gradient-pole technique, where the pole was positioned on a tripod so that its inlet could be lifted to different heights. The inlet was positioned manually with a repeatable accuracy of ± 1 cm between the surface and a maximum height of 1.6 m; see Held et al (2011b) for a detailed description.…”
Section: Sub-micrometer Aerosol Non-refractory Chemical Composition (mentioning
confidence: 99%